Pemanfaatan Kompos Jerami Padi dalam Pengembangan Bawang Merah di Ultisol Dataran Rendah Kota Padang - Nilla Kristina; Yusniwati, Yusniwati; Benni Satria; Elara Resigia; Aries Kusumawati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Shallots are a high-value horticultural commodity. But so far, they have been mostly developed in the highlands. Shallots are plants that like areas with hotter air temperatures, so they are suitable for cultivation in the lowlands. Still, the soil that is widely available in the lowlands of the city of Padang is Ultisol. Ultisol contains high clay, so the soil becomes dense, the available nutrients are low, and the ground has difficulty passing water. Using Ultisol as a land for planting shallots, it requires using organic fertilizer in large doses. One of the agricultural waste products that is available and has yet to be widely used in Lambung Bukik Village is rice straw. Rice straw is a waste that is difficult to decompose. Therefore, it is necessary to use a decomposer to get compost faster. Training on making rice straw compost and making demonstration plots was carried out in Lambung Bukik, Padang City, to support the development of shallot cultivation on lowland Ultisol. Farmers are very enthusiastic about learning to cultivate shallots and making organic fertilizer from rice straw.